Effect of Automatic Robotic Clutch on Clutch Lining Wear Characteristics Based on Tribology Testing - Billa Vandewa; Erwin Erwin; Didik Sugiyanto; Juan Pratama; Trisna Ardi Wiradinata (Universitas Medan Area, 2026)
The development of semi-automatic clutch systems, such as Automatic Robotic Clutch (ARC), aims to improve driving comfort in manual transmissions. However, changes to the clutch pressing mechanism can affect slip, working temperature, and clutch pad wear rate, so a tribological evaluation is required to ensure the vehicle's durability and performance. This study aims to analyze the effect of ARC installation on the wear rate of manual four-wheeled vehicle clutch pads by measuring run-out, thickness, and keeling nail depth. Tests are carried out on manual vehicles before and after ARC installation. The clutch lining is measured using the indrunout dial based on run-out and rivet depth. The engine's RPM performance is analyzed through sensor readings. The data are compared to identify changes in the wear of the C mounting, indicating an increase in clutch lining wear. This study shows that ARC affects clutch working characteristics in manual vehicles by increasing clutch slip during certain phases, thereby accelerating clutch lining wear as measured by run-out and rivet depth. It has an impact on the stability of vehicle RPM performance. This research contributes to the field of automotive and clutch tribology by providing experimental evidence of the impact of ARC on clutch lining wear, serving as a reference for the development of a more reliable semi-automatic clutch system.